State of the art on southern corn leaf blight disease incited by Cochliobolus heterostrophus: detection, pathogenic variability and novel control measures - Kutawa, Abdulaziz Bashir; Ahmad, Khairulmazmi; Ali, Asgar; Hussein, Mohd Zobir; Abdul Wahab, Mohd Aswad; Sijam, Kamaruzaman (National Center for Agrarian Sciences of Bulgaria, 2021)
Kutawa, A. B., Ahmad, Kh., Ali, A., Hussein, M. Z., Wahab, M. A. A., & Sijam, K. (2021). State of the art on southern corn leaf blight disease incited by Cochliobolus heterostrophus: detection, pathogenic variability and novel control measures. Bulg. J. Agric. Sci., 27 (1), 147–155. Corn is grown mainly for human utilization either in its fresh or processed form. However, the decline in the average corn yield has been attributed to the poor cultural practices, and this essentially involves failure to employ effective control measures. Southern corn leaf blight (SCLB) disease has been identified as one of the main challenges hampering corn yield. In this regards, the main focus of this paper is to critically review the recent studies on the SCLB pathogen detection, pathogenic variability and control methods. This includes a concise overview of the taxonomy, morphological and molecular characteristics as well as pathogenicity. More so, the recent advances in the control measures were diligently reviewed and reported in this paper. Southern corn leaf blight is a foliar disease caused by a fungal pathogen Bipolaris maydis, anamorph or Cochliobolus heterostrophus, teleomorph. Based on morphological characteristics, the colony colour of the pathogen was found to be grey, grey to green, dark grey and light grey. The conidial shape was elongated and it length and width ranges from 42-133 µm and 6-21 µm respectively. Both universal and specific primers were used to identify the pathogen using molecular method. The best method of controlling the disease is by using resistant varieties like brocade TSW and gang won, some new inbred lines (SLBR3 and SLBR5) were recently assessed to SCLB in Malaysia and found to be resistant to the disease. Moreover, Trichoderma harzianum (SH2303) and T. atroviride (SG3403) have shown a strong biocontrol activity against SCLB pathogen. Cultural practices like crop rotation and tillage helps immensely in minimizing the crop residues in corn growing farms.